Modelling the future low-carbon energy systems - case study of Greater Copenhagen, Denmark - Sara Ben Amer; Rasmus Bramstoft; Olexandr Balyk; Per Sieverts Nielsen (International Journal of Sustainable Energy Planning and Management, 2019)
In the light of insufficient climate policy on the global and national scale, ambitious cities are frontrunners of the climate action. Among them is Copenhagen, Denmark, aiming to achieve a CO2-neutral energy system in 2025. Reaching this goal requires, among other, changes in energy generation portfolio, which can be assessed using energy systems modelling. The aim of this study is to construct and evaluate four scenarios for sustainable electricity and heat supply of Greater Copenhagen and the new development project Nordhavn, deciding on the least expensive and least polluting option from a socio-economic perspective. Using the energy system model Balmorel, the energy scenarios are assessed and compared focusing on heat and electricity price and CO2 emissions. Sensitivity analyses are conducted considering changes in coefficient of performance (COP) of heat pumps and discount rate. The results show that from the socio-economic perspective, expanding district heating to Nordhavn is a promising solution. In case the heating demand in the Nordhavn area is supplied by a local source, power-to-heat technologies are chosen. Despite the narrow geographical focus, the challenges discussed in this paper and the method developed are relevant for other urban areas in Europe that aspire to have sustainable energy systems.